City-level hukou-based labor market discrimination and migrant entrepreneurship in China - Chen, Jie; Hu, Mingzhi (Technological and Economic Development of Economy, 2021)
A previously undocumented association between city-level degree of hukou-based labor market discrimination and migrant’s individual entrepreneurship engagement is examined. Applying the Oaxaca–Blinder decomposition analysis on the micro data from the China Migrants Dynamic Survey (CMDS) suggests that hukou-based labor market discrimination can on average explain a 6.3% differential in personal income for rural migrants relative to otherwise identical urban migrants. A one standard deviation increase in a city’s average hukou-based labor market discrimination is associated with roughly 2.9 percentage point higher of entrepreneurship rate among rural migrants, holding other things equal. Furthermore, city-level hukou-based labor market discrimination is associated with much higher propensity for engagement in necessitybased entrepreneurship compared with opportunity-based entrepreneurship. Our empirical work also suggests that the association between city-level hukou discrimination and migrant entrepreneurship is more prominent for people with middle level of education, young people, married people, and renters. Policy implications of these findings are discussed.First published online 05 July 2021